CloudProcMon: A Non-Intrusive Cloud Monitoring Framework - Syed, Hassan Jamil; Gani, Abdullah; Nasaruddin, Fariza Hanum; Naveed, Anjum; Ahmed, Abdelmuttlib Ibrahim Abdalla; Khurram Khan, Muhammad (Institute of Electrical and Electronics Engineers, 2018)
Cloud computing has seen massive growth in this decade. With the rapid development of cloud networks, cloud monitoring has become essential for running cloud systems smoothly. Cloud monitoring collects monitoring metrics from the cloud's physical and virtual infrastructures. In terms of data collection, cloud monitoring can be intrusive or non-intrusive. Monitoring data collection non-intrusively from the host operating system (OS) is a challenging task. The aim of this paper was to collect monitoring data from the host OS non-intrusively and to link those data with the cloud controller for use in monitoring. Monitoring data were collected from Procfs of the host OS and that information was linked with the monitoring dashboard on the cloud controller node. The results show that the proposed solution is an efficient, lightweight, and scalable cloud monitoring framework that produces negligible overhead.